DISTRIBUTION OF URBAN SURFACE TEMPERATURES IN CAICO / RN - Maria, Rosangela [UNESP]; Amorim, Margarete Cristina de Costa Trindade [UNESP]; Martin, Encarnita Salas [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2016)
There are many environmental problems that permeate the spaces of the city, as well as the possible elements that could be considered as causing indicators, and/or enhancers of those problems. Thus, we propose here a qualitative analysis of the intra-urban temperatures in winter episodes in the city of Caico/RN, from the use of the image of the thermal infrared channel, band 10, Landsat-8 satellite. For this purpose, literature reviews were conducted on the subject at the agenda, survey data on the physical and social characteristics of the study area and image processing, for preparing the surface temperature chart of the urban perimeter. The results showed a predominance of higher temperatures in areas with exposed soil, followed by areas with fragmented vegetation cover and areas with concentration of buildings. The milder temperatures were checked in areas with presence of vegetation and water bodies.
Keywords: intra-urban temperatures; Channel thermal infrared; Vegetal cover; Water bodies; Caico/RN